Implementation of the Balanced Scorecard Approach in Industries: A Systematic Literature Review - Dias Sukma Irawati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2020)
A systematic review is a method used by researchers to identify, assess, and interpret all findings on research topics to be understood from various research perspectives before the researcher conducted the primary research. This article aims to determine which areas the Balanced Scorecard has used and applied using a systematic review method. The Balanced Scorecard is a concept for measuring the performance of an organization with four different perspectives. The preliminary article screening technique used is to review research papers with the keyword "Balanced Scorecard." 30 articles apply the balanced scorecard in various fields, including health, industry, transportation, finance, business, and management. From the financial and customer perspectives, there are 11 journals each. There are eight journals and 11 journals from internal business processes. The balanced scorecard theory, which is presented in 4 different perspectives, makes the balanced scorecard a balance between measuring an organization's performance in various fields.